The Legal Implications for Authentic Deeds Declared to be False - Royce, Pasma; Sudiro, Amad (Universitas Islam Sultan Agung, 2024)
A notary is an official who is authorized to make authentic deeds. An authentic deed is a deed whose proof is strong in court. As a Notary, caution is important, because the Notary is responsible for the deed and the parties who sign the deed. The problem faced in this study is how to be responsible for the falsification of the contents of the deed and signatures carried out by the parties by the notary and the plaintiff in the Surabaya District Court Decision Number 237/Pid.B/2021/PN. Sby and what are the legal implications for authentic deeds that are declared fake in the Surabaya District Court Decision Number 2370/Pid.B/2021/PN. Sby. The research method used in this writing is the research of normative juridical law. The results of the study show that if a Notary while carrying out his office commits a violation that causes losses to the parties or third parties, then a Notary can be sanctioned in the form of civil sanctions contained in Article 84 and sanctions of the code of ethics for the position of Notary or administrative in Article 85. The Notary Position Law only regulates Civil Sanctions and Code of Ethics Sanctions for Notary Positions, it does not mention the existence of Criminal Sanctions that can be given to a Notary. However, criminal sanctions can also be imposed on the Notary, if the act committed meets the elements of a criminal act. As with the process of imposing witnesses, it is necessary to prove the charges that are accused of the Notary, which in the imposition of witnesses and the authority to examine and adjudicate is the code of ethics assembly, while the criminal sanctions or civil sanctions that examine and adjudicate are the courts. Legal implications for authentic deeds that are deliberately filled with false information in their creation, the notary deed is null and void by court decision and the deed becomes degraded from the original authentic deed to a deed under hand.